Severity assessment tools for predicting mortality in hospitalised patients with community-acquired pneumonia. Systematic review and meta-analysis. Issue 10 (20th August 2010) - Chalmers, James D; Singanayagam, Aran; Akram, Ahsan R; Mandal, Pallavi; Short, Philip M; Choudhury, Gourab; Wood, Victoria; Hill, Adam T
Abstract : Introduction: International guidelines recommend a severity-based approach to management in community-acquired pneumonia. CURB65, CRB65 and the Pneumonia Severity Index (PSI) are the most widely recommended severity scores. The aim of this study was to compare the performance characteristics of these scores for predicting mortality in community-acquired pneumonia. Methods: A systematic review and meta-analysis was conducted according to MOOSE (meta-analysis of observational studies in epidemiology) guidelines. PUBMED and EMBASE were searched (1980–2009). 40 studies reporting prognostic information for the PSI, CURB65 and CRB65 severity scores were identified. Performance characteristics were pooled using a random effects model. Relationships between sensitivity and specificity were plotted using summary receiver operator characteristic (sROC) curves. Results: All three scores predicted 30 day mortality. The PSI had the highest area under the sROC curve, 0.81 (SE 0.008), compared with CURB65, 0.80 (SE 0.008), p=0.1, and CRB65, 0.79 (0.01), p=0.09. These differences were not statistically significant. Performance characteristics were similar across comparable cut-offs for low, intermediate and high risk for each score. In identifying low risk patients, PSI (groups I and II) had the best negative likelihood ratio 0.08 (0.06–0.12) compared with CURB65 (score 0–1) 0.21 (0.15–0.30) and CRB65 (score 0), 0.15 (0.10–0.22). Conclusion: There were no significant differences in overall test performance between PSI, CURB65 and CRB65 for predicting mortality from community-acquired pneumonia.